Crosstalk between cancer and haemostasis - Langer, F.; Bokemeyer, C. (Hämostaseologie, 2012)
Cancer is characterized by bidirectional interrelations between tumour progression, coagulation activation, and inflammation. Tissue factor (TF), the principal initiator of the coagulation protease cascade, is centrally positioned in this complex triangular network due to its pleiotropic effects in haemostasis, angiogenesis, and haematogenous metastasis. While formation of macroscopic thrombi is the correlate of cancer-associated venous thromboembolism (VTE), a major healthcare burden in clinical haematology and oncology, microvascular thrombosis appears to be critically important to blood-borne tumour cell dissemination. In this regard, expression of TF in malignant tissues as well as shedding of TFbearing microparticles into the circulation are thought to be regulated by defined genetic events relevant to pathological cancer progression, thus directly linking Trousseau’s syndrome to molecular tumourigenesis.Because pharmacological inhibition of the TF pathway in selective tumour types and patient subgroups would be in line with the modern concept of individualized, targeted anti-cancer therapy, this review will focus on the role of TF in tumour biology and cancer-associated VTE.
Keywords: Cancer; thrombosis; tissue factor; micro- particles